STUDI ETNOGRAFI PERILAKU PENGEMIS MASYARAKAT DESA PRAGAAN DAYA KABUPATEN SUMENEP - Rina Hardiyantina; Sukardi Sukardi (Universitas Merdeka Malang, 2016)
Pragaan Daya village in Sumenep Regency is known as the village of beggars, for begging into people's daily work. Which became the main motive for people to do the work of begging is behavior